1996
DOI: 10.1021/jp961821m
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Ether Oxidation:  Kinetics and Mechanism of the CH3OCH2 + O2 Reaction at 296 K and 0.38−940 Torr Total Pressure

Abstract: The title reaction was studied at 296 K and 0.38-940 Torr total pressure using a FTIR smog chamber technique. The overall rate constant for reaction of CH 3 OCH 2 radicals with O 2 may be written, k 1 ) k RO2 + k prod , where k RO2 is the rate constant for peroxy radical production and k prod is the rate constant for the production of other species from reaction 1. k 1 was measured relative to the pressure independent reaction of CH 3 OCH 2 radicals with Cl 2 (k 4 ). There was no discernible effect of pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 19 publications
13
108
1
Order By: Relevance
“…This mechanism is analogous to that proposed to explain the production of OH in the reaction of O 3 with alkenes [27] and in the reaction of CH 3 OCH 2 with O 2 [28,29]. The ultimate fate of the biradical, CH 2 C(O)O, is unknown.…”
Section: Product Yields From Cl-initiated Oxidation Of Acetaldehyde Isupporting
confidence: 55%
“…This mechanism is analogous to that proposed to explain the production of OH in the reaction of O 3 with alkenes [27] and in the reaction of CH 3 OCH 2 with O 2 [28,29]. The ultimate fate of the biradical, CH 2 C(O)O, is unknown.…”
Section: Product Yields From Cl-initiated Oxidation Of Acetaldehyde Isupporting
confidence: 55%
“…The thin broken line shows CH 2 O yield based on G2-determined properties. Both calculation methods underestimate the rate constant compared to data of Sehested [2]. A QRRK fall-off plot matching the data of Sehested is obtained by lowering the E a for TS2 by 3.3 kcal/mol with CBS-q-determined thermodynamic properties.…”
Section: Qrrk Calculation Results and Ch 2 O Yieldmentioning
confidence: 81%
“…The comparison of formaldehyde yields with CBS-q, G2, and experimental data are shown in Figure 6. The asterisk symbol represents experimental data of Sehested et al at 296 K and 0.38 to 940 Torr total pressure [2]. The thin continuous line shows CH 2 O yield based on CBS-q-determined thermodynamic properties.…”
Section: Qrrk Calculation Results and Ch 2 O Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Then this latter concentration was considered to be suitable to prevent the RЉ ϩ Cl 2 reaction without decreasing the detection sensitivity of Cl atoms too much. In the case of DME, Sehested et al [15] reported a ratio of k(CH 3 OCH 2 ϩ O 2 )/k(CH 3 OCH 2 ϩ Cl 2 ) ϭ (0.06 -0.07) in the pressure range 15 -60 Torr. By using this ratio for our experimental conditions, we obtain (k(CH 3 …”
Section: ϫ3mentioning
confidence: 99%